Experimental murine mycobacteriosis: evaluation of the functional activity of alveolar macrophages in thalidomide- treated mice - Arruda, M.S.P. [UNESP]; Richini, V.B. [UNESP]; Oliveira, S.M.A. [UNESP]; Vilani-Moreno, F.R. (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
Thalidomide is a selective inhibitor of tumor necrosis factor-alpha (TNF-alpha), a cytokine involved in mycobacterial death mechanisms. We investigated the role of this drug in the functional activity of alveolar macrophages in the presence of infection induced by intranasal inoculation of Mycobacterium avium in thalidomide-treated and untreated adult Swiss mice. Sixty animals were inoculated with 5 x 10(6) M. avium by the respiratory route. Thirty animals received daily thalidomide (30 mg/kg mouse) and 30 received water by gavage up to sacrifice. Ten non-inoculated mice were used as a control group. Lots of animals from each group were evaluated until 6 weeks after inoculation. Infection resulted in an increased total number of inflammatory cells as well as increased activity of pulmonary macrophages. Histologically, intranasal inoculation of bacilli resulted in small mononuclear infiltrates located at the periphery of the organ. Culture of lung fragments revealed the presence of bacilli only at the beginning and at the end of the experimental period. Thalidomide administration did not affect the microbiological or histological features of the infection. Thalidomide-treated and untreated animals showed the same amount of M. avium colonies 3 weeks after infection. Although it did not affect bacillary clearance, thalidomide administration resulted in a decreased percent of spread cells and release of hydrogen peroxide, suggesting that factors other than TNF-alpha play a role in the killing of mycobacteria by alveolar macrophages. Thalidomide administration also reduced the number of spread cells among resident macrophages, suggesting a direct effect of the drug on this phenomenon.
Keywords: Mycobacterium avium; Alveolar macrophages; Thalidomide; Experimental infection